ANALISIS USER EXPERIENCE WEBSITE BIRO PENGADAAN BARANG DAN JASA PROVINSI SUMATERA SELATAN MENGGUNAKAN METODE HEURISTIC EVALUATION - Rasmila; Ario Damsi; Rahmat Novrianda Dasmen (Tech-E, 2026)
This study evaluates user experience (UX) on the South Sumatra Province Goods and Services Procurement Bureau (PBJ) website using Jakob Nielsen’s Heuristic Evaluation to identify usability barriers affecting e-government transparency and accountability. As public procurement increasingly relies on digital platforms, preliminary assessments revealed critical issues including unintuitive navigation, limited system feedback, and inadequate user guidance that risk undermining public trust. The evaluation employed a 30-item Likert-scale questionnaire aligned with ten heuristic principles and was conducted by expert evaluators. The results show an overall usability index of 81, classified as excellent, with strong performance in consistency and standards (92 percent) and aesthetic and minimalist design (88 percent). Nevertheless, lower scores emerged in help and documentation (69 percent) and error prevention (78 percent), indicating priority areas for improvement. The findings confirm that usability heuristics function as governance enablers rather than purely technical attributes. Improved visibility of system status and effective error recovery mechanisms enhance procurement oversight and are associated with a 20 to 30 percent reduction in vendor drop-off rates. Contextual tooltips and guidance further strengthen accountability in high-value public tenders. The study recommends simplifying navigation structures, strengthening form validation, and implementing searchable frequently asked questions for sustainable provincial e-government implementation initiatives.